THE EFFICIENT SYNTHESIS OF POLY(SILAPROPYNYLENES) VIA CONDENSATION OF NACCNA WITH R1R2SICL2 ACTIVATED BY PYRIDINE - JO, SM; LEE, WS; LYU, HS (SPRINGER VERLAG, 1993)
To efficiently prepare poly(silapropynylenes), the condensation of NaC=CNa with R1R2SiCl2 activated by pyridine were investigated. The condensation produced tactable polymers(Mw ca. 2100-9000) with significantly higher yields of 80-97% than those from R1R2SiCl2 itself and also gave rise to much more improvement in the yields and molecular weight than with acetylenic ''di Grignard'' or ''di lithium salts''. The activation of R1R2SiCl2 by pyridine accelerated the condensation reaction, which resulted in production of macrocyclic polymers as well as linear polymers.
Keywords: ORGANO-SILICON COMPOUNDS; CHEMISTRY; POLYMERS